Antioxidant activity of ethanolic extract of Euphorbia thymifolia linn. - Prabha T.; Singh S.K. (My University, 2025)
The antioxidant activity of the ethanol extract of the whole plant of Euphorbia thymifolia Linn. has been evaluated in both in vivo and in vitro experimental models, by estimating the malondialdehyde content of rat brain, which is one of the products of the lipid peroxidation. The ethanolic extract of the plant showed significant inhibition of lipid peroxidation level comparable to that of Vitamin E used as standard.